Analisis Motivasi Belajar Matematika Siswa Sekolah Dasar di Desa Mangki Kecamatan Cempa Kabupaten Pinrang - Mukhlisa, Nurul; Hasan, Kamaruddin; Mahmud, Suriadi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to determine mathematics learning motivation of elementary school students’ at Mangki Village, Cempa District, Pinrang Regency. This is descriptive research with quantitative approach. Population in this study is all of elementary school students at Mangki Village as many as 141 students and 59 students as sample. Research instrument was questionnaire with 36 statements adapted from ARCS questionnaire by Keller. Data was analyzed by descriptive statistics. Result of data analysis showed the largest percentage of students’ mathematics learning motivation was 50,85% and belongs to high motivation category. It can be concluded that mathematics learning motivation of elementary school students’ at Mangki Village in high category.